2017
DOI: 10.1002/ijc.30899
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis following cancer surgery during holiday periods

Abstract: Surgery is the mainstay curative treatment in most cancer. We aimed to test the new hypothesis that cancer surgery performed during holiday periods is associated with worse long-term prognosis than for non-holiday periods. This nationwide Swedish population-based cohort study included 228,927 patients during 1997-2014 who underwent elective resectional surgery for a cancer where the annual number of resections was over 100. The 16 eligible cancer sites were grouped into 10 cancer groups. The exposure, holiday … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Treatment delay is associated with survival in patients with bladder cancer subjected to RC. Thus there is evidence that, to improve survival, centralisation of RC care should be combined with maintaining high hospital volume and consistent care over seasons , and ensuring a treatment delay of <3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment delay is associated with survival in patients with bladder cancer subjected to RC. Thus there is evidence that, to improve survival, centralisation of RC care should be combined with maintaining high hospital volume and consistent care over seasons , and ensuring a treatment delay of <3 months.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Although it is difficult to identify a cause-effect relationship, this paper is in line with multiple others on the same topic assuming that specific cultural and environmental factors (e.g., vacations) might play a major role in medical and surgical outcomes [ 10 12 ].…”
Section: Discussionmentioning
confidence: 75%
“…A third mechanism that can explain seasonal variations in surgical outcomes is staff and resource shortage during vacation periods. Several studies have demonstrated worse outcomes for procedures performed on Fridays [10], on weekends [11] or during vacation or holiday periods [12], regardless of the specific month in which they take place worldwide [30,31]. During holidays, hospital systems are significantly disrupted, as significant segments of the staff are off work and care capacity is usually delivered by less experienced/occasional staff and with less overall resource availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Patients who underwent esophagectomy during holiday periods did not seem to have any worse survival than those who had surgery during non-holiday periods according to two population-based and nationwide Swedish cohort studies. 32,33 Summary of Surgeon-Related Factors. Surgeon volume seems to have a substantial influence on the chance of longterm survival after esophagectomy for esophageal cancer.…”
Section: Surgeon-related Factors In Relation To Long-term Survival Inmentioning
confidence: 99%